5x+2=625
Nguyễn thị kim oanh nè,bài của cậu đây.
Tính nhanh:
(75 x 625+175 x 625) : (20 x 25 x 125 - 625 x 75)
Cách làm:
(75 x 625+175 x 625) : (20 x 25 x 125 - 625 x 75)
=625 x (175+75) : (20 x 5 x 125 x 5 - 625 x 75)
=(625 x 250) : (20 x 5 x 625 - 625 x 75)
=(625 x 250 : (100 x 625 - 625 x 75)
=(625 x 250) : (625 x (100-75))
=(625 x 250) : (625 x 25)
=10
Tìm x:25<5^:5^2<625
5^x . (5^3)^2 = 625
5x.5x+2= 625
\(5^x.5^{x+2}=625\)
\(\Leftrightarrow5^{2x+2}=5^4\)
\(\Leftrightarrow2x+2=4\)
\(\Leftrightarrow x=1\)
Vậy ..
5x.5x+2 =625
5x.5x.52 =625
5x+x.25 =625
52x.25 =625
52x =625:25
52x =25
52x = 52
⇒2x =2
x =2:2
x =1
Vậy x=1
tìm x biết
5^x+5^x+2=625
tim x 5x+5x+2=625
5x+2-5x+1-5x= 625
( 2 . x - 5 ) ^ 2 = 625
\(\left(2x-5\right)^2=625\)
\(\left(2x-5\right)^2=25^2=\left(-25\right)^2\)
TH1: \(2x-5=25\)
\(2x=30\)
\(x=15\)
TH2 : \(2x-5=-25\)
\(2x=-20\)
\(x=-10\)
Vậy \(x\in\left\{-10,15\right\}\)
=.= hok tốt!!
\(\left(2.x-5\right)^2=625\)
\(\left(2.x-5\right)^2=25^2\) hoặc \(\left(2.x-5\right)^2=\left(-25\right)^2\)
\(\Rightarrow\)\(2.x-5=25\) \(\Rightarrow\) \(2.x-5=-25\)
\(2.x=25+5\) \(2.x=-25+5\)
\(2.x=30\) \(2.x=-20\)
\(x=30\div2\) \(x=-20\div2\)
\(x=15\) \(x=-10\)
Vậy \(x=15\) ; \(x=-10\)
\(\left(2x-5\right)^2=625\)
\(\left(2x-5\right)^2=25^2\)
=> \(\left[{}\begin{matrix}2x-5=25\\2x-5=-25\end{matrix}\right.\) \(\) <=> \(\left[{}\begin{matrix}2x=30\\2x=-20\end{matrix}\right.\) <=> \(\left[{}\begin{matrix}x=15\\x=-10\end{matrix}\right.\)
_Vậy x = 15 hoặc x = -10
a) 3\(^{x-1}\)+3\(^x\)+3\(^{x+1}\)=1053
b) 5\(^{x-2}\).5\(^x\).5\(^{x+2}\).5\(^{x+4}\)= 625
giúp mình nha
a) \(3^{x-1}+3x+3^{x+1}=1053\)
\(=3^x:3+3^x+3^x.3=1053\)
\(=3^x.\dfrac{1}{3}+1+3=1053\)
\(=3^x.\dfrac{13}{5}=1053\)
\(=3^x=243\)
\(\Rightarrow x=5\)
Vậy \(x=5\)
5^x . (5^3)^2 = 625
Tìm x:
5x . (53)2 = 625
5x . 56 = 54
5x+6 = 54
=> x + 6 = 4
=> x = 4 - 6
x = -2
Vậy x = -2
Ủng hộ mk nha !!!! ^_^
5x . (53)2 = 625
5x . 56 = 54
5x = 54 : 56
5x =
5x . ( 53 )2 =625
5x . 56 = 54
5x + 6 = 54
x + 6 = 4
x = 4 - 6
x = -2